2006
DOI: 10.1002/anie.200600483
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Reactions of Highly Strained 2,3‐Bridged 2H‐Azirines

Abstract: Take the strain: Despite extreme ring strain and reactivity, the heterocycles 2, which are easily obtained from azides 1 and detectable by NMR spectroscopy, can be converted stereoselectively by novel addition and cycloaddition reactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
16
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 46 publications
1
16
0
Order By: Relevance
“…Davis also noted that other N ‐tosyl aziridines can rearrange to vinylic amines; both processes are thought to begin with α‐deprotonation of the aziridine. Note that the highly strained bicyclic azirine that would form from aziridines 5 and 7 – 9 has only recently been detected spectroscopically, in situ , by Banert and Meier 27. Another possible decomposition pathway, reductive alkylation, was reported by O'Brien for aziridines treated with sec ‐butyl lithium;17 however, the likelihood of the bulky diisopropylamide exhibiting this reaction is low.…”
Section: Resultsmentioning
confidence: 95%
“…Davis also noted that other N ‐tosyl aziridines can rearrange to vinylic amines; both processes are thought to begin with α‐deprotonation of the aziridine. Note that the highly strained bicyclic azirine that would form from aziridines 5 and 7 – 9 has only recently been detected spectroscopically, in situ , by Banert and Meier 27. Another possible decomposition pathway, reductive alkylation, was reported by O'Brien for aziridines treated with sec ‐butyl lithium;17 however, the likelihood of the bulky diisopropylamide exhibiting this reaction is low.…”
Section: Resultsmentioning
confidence: 95%
“…It was found that water [37], Brønsted [44,48] and Lewis acids [4041 43] facilitate the formation of pyrazine derivatives. 2 H -Azirines undergo ring opening on electronic excitation to give nitrile ylides [50].…”
Section: Resultsmentioning
confidence: 99%
“…3 ) that the reaction involving dihydropyrazines 11 on the way to 4 and 5 could be quite competitive with the reaction leading to 3 , provided that a source of dihydropyrazines 11 is available. Formation of ‘dimer azirines’, dihydropyrazines [ 37 41 ], or products of their dehydrogenation, pyrazines [ 37 49 ] under different conditions is quite common. Moreover, everybody who works with 3-aryl-2 H -azirines faces the problem of their storage, because these compounds, both with unsubstituted and an electron-donor substituted benzene ring, fast transform into pyrazines, even when stored in a fridge.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, when the cyclic enaminone D was treated with PhI(OAc) 2 under identical conditions, the formation of the aromatic C-N bond occurred to give the carbazolone compound E. The corresponding 2Hazirine F was not formed due to its highly strained bridged-ring system. 11 This unexpected finding revealed a complementary route to the construction of the important carbazolone skeleton (Scheme 1).…”
mentioning
confidence: 94%